Effect of nanofibers at surface of carbon fibers on microstructure of carbon/carbon composites during chemical vapor infiltration - Xiao, Peng; Chen, Jie; Xu, Xian-feng; Lu, Xue-feng (Journal of Central South University, 2014)
Before densification by chemical vapor infiltration, carbon or SiC nanofibers were grown on the surface of carbon fibers by catalytic chemical vapor deposition using electroplated Ni as catalyst. The modification and mechanism of nanofibers on the pyrocarbon deposition during chemical vapor infiltration were investigated. The results show that the nanofibers improve the surface activity of the carbon fibers and become active nucleation centers during chemical vapor infiltration. They can induce the ordered deposition of pyrocarbon and adjust the interface bonding between pyrocarbon and carbon fibers during the infiltration.